2021
DOI: 10.3390/s21072521
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range UHF RFID Tag for Automotive License Plate

Abstract: In this paper, various locations of an Ultra High Frequency (UHF) Radio Frequency Identification (RFID) tag on automotive license plates have been considered based on the radiation pattern of the tag antenna. A small, 130 × 50 mm, passive loop antenna type UHF RFID tag for an automotive license plate was simulated with an EM simulation CST program. It was designed to have a larger back-lobe radiation pattern since the front side of the tag faces the back side of the plate holder to protect the tag antenna from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…One of the problems raised in the literature is the hardware support in heterogeneous physical RFID infrastructures, which is why mechanisms and protocols (such as LLRP.) need to be implemented and integrated in middleware architectures in order to guarantee a better hardware abstraction Real-time RFID analysis Collecting, processing, exploiting, visualising, extracting information from big RFID data in real time to make decisions, is detected among the challenges of RFID applications Chung and Berhe, (2021). And from the literature review it was found that none of the existing architectures address this aspect.…”
Section: Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation
“…One of the problems raised in the literature is the hardware support in heterogeneous physical RFID infrastructures, which is why mechanisms and protocols (such as LLRP.) need to be implemented and integrated in middleware architectures in order to guarantee a better hardware abstraction Real-time RFID analysis Collecting, processing, exploiting, visualising, extracting information from big RFID data in real time to make decisions, is detected among the challenges of RFID applications Chung and Berhe, (2021). And from the literature review it was found that none of the existing architectures address this aspect.…”
Section: Heterogeneitymentioning
confidence: 99%
“…Among the most widely adopted evaluation methods for middleware is the use of application examples to quantitatively evaluate the performance of the system based on the number of lines of code (Haibi et al, 2018), but this method has certain limitations (Chung and Berhe, 2021). The most efficient method is to evaluate the middleware according to certain required functionalities.…”
Section: Evaluation and Comparisonsmentioning
confidence: 99%
“…This technology is becoming more and more popular in everyday life. It has been extensively used in many practical applications in Internet of Things (IoT) and has become essential for a set of applications including identification, localization, tracking, sensing, inventory control, and supply chain management [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of such a system depends primarily on the correct design of the transponder antenna. The subject of RFID antenna synthesis has been discussed frequently in the research literature; consideration of the design of an effective electronic tag is not new [2][3][4][5][6]. Unfortunately, there are no universal 'off-the-shelf' devices that could be used directly in non-standard utility applications.…”
Section: Introduction 1object Under Investigationmentioning
confidence: 99%
“…Unfortunately, there are no universal 'off-the-shelf' devices that could be used directly in non-standard utility applications. That is why many designs dedicated to specific applications (e.g., automotive [4] or pharmacy [5]), or that can work in a specific environment (e.g., near metals [2,3,6]), have been developed. In practical applications, in terms of engineering tasks, such designs are possible because the structure and operation of the specified object is precisely known, so the input parameters for numerical models of RFID antennas can be readily defined.…”
Section: Introduction 1object Under Investigationmentioning
confidence: 99%